Simplified Calculation of Energy Efficiency Index for Plate Heat Exchanger. Issue 1 (August 2020) - Lu, Hongliang; Ren, Bin; Pu, Zhe; Si, Jun; Ren, Facai; Du, Yannan
Abstract: Based on GB/T 27698.3-2011 heat exchanger and heat transfer element performance test method Part 3: Plate heat exchanger, a simplified method for the calculation of energy efficiency index is proposed other than just experimental data required by NB/T 47004.1-2017 plate heat exchangers-part 1: plate-and-frame heat exchangers. The new equation of EEI in term of 12 parameters δρ, λρ, lh, l c, dh, d c, Ch, Cc, ah, bh, ac, bc incorporates both fitted correlations of experimental result and parameters for fluid physical properties and working conditions. Therefore, the method omits the intermediate processes such as total heat transfer coefficient k and pressure drops for both sides. It also solves the accuracy problem that deviates from the standard working conditions and is difficult to realize practically. The new test of high cost is unnecessary to obtain the energy efficiency index for old plate heat exchangers with part experimental data or correlations.